Pendidikan kesehatan gigi / Eliza Herijulianti, Tati Suasti Indriani, Sri Artini ; editor, Monica Ester - HERIYULIANTI, Eliza ; TATI SVASTI INDRIANI ; SRI ARTINI ; MONICA ESTER (EGC, 2002)
x, 152 halaman ; 21 cm